Faktor Penyebab Terjadinya Tindak Pidana Korupsi Serta Dasar Pertimbngan Hakim Terhadap Putusan Bebas Pada Perkara Korupsi Dalam Surat Putusan No. 40/Pid/Sus-TPK/2020/PN-KPG - Nani Raga, Lukas Stefanus; Leo, Rudepel Petrus; Amalo, Heryanto (Artemis Law Journal, 2024)
The Defendant in the Corruption Case on Land belonging to the Kupang City Government, Thomas More, committed a criminal act of corruption with witness Jonas Salean in accordance with the contents of the Kupang Class IA District Court decision in 2020 and in this case the Defendant and the Witness in question issued the land title certificate and signed the assets. belongs to the State in order to enrich oneself, so that in the District Court decision letter Number: 40/Pid/Sus-TPK/2020/PN-KPG. The defendant Thomas More was sentenced to a criminal sentence while the witness Jonas Salean was given an acquittal. The main problems in this research are: (1) What are the factors that cause the occurrence of criminal acts of corruption? (2) What is the basis for the judge's consideration in handing down an acquittal decision in this case? This research is empirical legal research, namely reviewing and analyzing data obtained from the research location. The results of this research show that (1) the factors causing corruption in land belonging to the Kupang City Government are (a) Internal Factors, namely the feeling of wanting to enrich oneself. (b) External Factors, namely the existence of opportunities/opportunities which are seen from the position of the defendant at the time of committing the crime corruption and also the closeness of the defendant to witnesses who participated in committing criminal acts of corruption. (2) The basis of consideration used by the judge in handing down an acquittal decision is seen from: (a) the elements of the primary indictment article and (b) the elements of subsidiary coercion.